Retention of Gap Length in Normal-Hearing Listeners. (September 2013) - Ries, Dennis T; Woods, Audra; Smith, Meghan
Listener retention of silent, gap-length duration was studied. Just noticeable differences (JNDs) for gap length within standard and comparison stimuli were obtained for intervals with and without intervening noise bursts, including a condition with gapped intervening bursts. Outcomes indicate that gap duration itself can be determinant. Also, JNDs were similar whether intervening stimuli were present or absent, differing from results reported for pitch, loudness, and timbre retention. The latter suggests additional/alternative cortical resources might be employed for retention of auditory–temporal information.